Resistance Training Recommendations to Maximize Muscle Hypertrophy in an Athletic Population: Position Stand of the IUSCA. (2021) - Schoenfeld, Brad; Fisher, James; Grgic, Jozo; Haun, Cody; Helms, Eric; Phillips, Stuart
No abstract available